P61 Assessment of clinically significant portal hypertension among periportal fibrosis versus liver cirrhosis patients using fibroscan. (19th June 2022) - Allam, Dalia; Abdalla, Hala; Allam, Dalia
Abstract : Introduction: Assessment of clinically significant portal hypertension (PHTN) is a important step in the evaluation of newly diagnosed advanced chronic liver disease (ACLD) and in periportal fibrosis patients. The current gold standard method of assessment includes the invasive evaluation of hepatic venous pressure gradient (HVPG) and endoscopy. However, non invasive techniques like fibroscan have been proposed and well established to stratify and monitor patients with portal hypertension without undertake repeated invasive assessment. Objective: To assess clinically significant portal hypertension among periportal fibrosis patients versus liver cirrhosis patients using fibroscan. Methods: This is a case control study . 409 patients were enrolled, they were divided into three groups .patients diagnosed with periportal fibrosis (PPF) secondary to Schistosomiasis 156 patients, while Liver cirrhosis(LC) group include 150 patients and control group 103) patients . Data regarding; demographics, diagnosis, bleeding history, evidence of decompensation, laboratory investigations, abdominal ultrasound, endoscopic finding, assessment of liver stiffness using fibroscan, and 6 weeks mortality were collected. Results: In total this study enrolled 409 participants, 156 with PPF (57.1% males and 42.9% females; mean age= 47±12.5 years), 150 patients with liver cirrhosis (LC) (62.7% males and 37.3% females; mean age= 49.5±14.5 years), and 103 normal control individuals (62.1% males and 37.9% females; mean age= 46±13 years). The rate of bleeding was higher in PPF patients more than LC patients (77.6% vs 52.7%; P= 0.000). The evidences of decompensation was elevated in LC more than PPF group (58% vs 19.2%; P= 0.000). The highest means of Fibrosis (F) scores using fibroscan were found among liver cirrhosis (LC) (36.2±20 KPa) and PPF groups (19.5±5.3 KPa) while the lowest mean was found among controls (4.5±0.8 KPa) (P= 0.000). By using cut-off values of F score (19.2 KPa) for LC and (14.9 KPa) for PPF to detect CSPH the AUC were 0.980(95%CI: 0.968 – 0.991; sensitivity 74%, specificity 77%) and 0.917(95%CI: 0.879 – 0.954; sensitivity 77%, specificity 80%), respectively. As shown in the following table 1 . The means of F score was significantly higher in bleeders more than non-bleeders in both LC and PPF groups (P= 0.002 for LC group and 0.000 for PPF group) .Moreover among patients with massive ascites (P= 0.004 for LC group and 0.027 for PPF groups), HE grade – II (P= 0.002 for LC group and 0.038 for PPF group), spontaneous bacterial peritonitis (P= 0.0.21), and hepatocellular carcinoma (P= 0.024). The highest mean of F score were found among patients with OV-III and IV (P= 0.000 for LC and PPF group) as well as patients with PHTN gastropathy and fundal varices in LC groups (P= 0.000). The highest mean of F score were found among dead patients comparing to alive (P= 0.000 for LC and PPF group). Conclusions: This Study concluded that, PHTN in LC patients was significantly associated with evidence of decompensation and mortality, while in PPF patients .it was associated with Variceal bleeding, splenomegaly and portal vein thrombosis (PVT). In Fibroscan, using cut off values of (19.2 KPa) for LC and (14.9 KPa) for PPF were found to be accurately detected clinically significant PHTN. F scores of Transient Elastography was significantly correlated with Variceal bleeding, massive ascites, advanced HE, spontaneous bacterial peritonitis, hepatorenal syndrome, and hepatocellular carcinoma.